Land Capability Classification For Land Evaluation : A Review - SANTUN R.P SITORUS (Jurnal Sumberdaya Lahan, 2010)
Land capability classification has been used for land evaluation for various purposes in many countries in the world. Since developed by the United States Department of Agriculture as a part of the programme to control soil erosion, the land capability classification has been further developed by a number of authors in many countries to suit their requirements. Of the numerous land capability classification have been published, fourteen are selected to be reviewed. The results shows that the aims of the various land capability classification schemes are generally similar: to evolve methodology whereby land may be evaluated for a particular land use purposes. Most of the methodologies were designed mainly for evaluating the capability of land for agriculture, either in narrow (specific) or in broad terms (including forestry, pasture, etc). Three methods of evaluation of data can be identified: Firstly, descriptive methods whereby capability classes or other categories are descriptive solely in words. Secondly, rating, grading or indexing system whereby each attribute is assigned a rate, grade or index and the capability class or other category is defined in terms of the sum of the weighted scores. Thirdly, quantitative methods whereby the relationships between variables are defined in terms of an equation used to obtain a score or index which defines the capability class or other categories. The capability methods also vary both as hierarchical systems and in terms of the number of categories used. They are also vary in terms of scale, and some do not even specify the scales used. Although substantial differences are found among the methodologies in terms of their purposes and detailed procedures, these are all broadly similar in terms of the general approach and activities involved.